TIPOLOGI POLA SPASIAL DAN SEGREGASI SOSIAL LINGKUNGAN PERMUKIMAN CANDI BARU - Setyohadi K., Bambang (Semarang State University, 2007)
Settlement environment asthe receptacle of essence societies life is a produce of people culture materialism. Result of tectonies between culture aspect and built environment thats running as comprehensivly. Candi Baru settlement as receptacle of tectonies above full of people culture element in assuming natural condition. Space structure thats unique with social segregation division (elite, neutral, bottom) to be valuable its era. Space gradation in concept where in the rear of under line settlement in the pattern of Kampung Kota